Analisis Kapabilitas Pemasaran E-Commerce Dalam Menciptakan Efektivitas Promosi Dan Strategi Bersaing (Studi Kasus pada UMKM Sektor Perdagangan Kota Sukabumi) - Anak Agung Putu Ayu Inggriyani; R Deni Muhammad Danial; Acep Samsudin (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of E-commerce marketing capabilities in creating the effectiveness of promotions and competitive strategies carried out on SMEs in the trading sector in Sukabumi City. The research method used is a quantitative method with a descriptive and associative approach, The sample used is 70 companies that have met the criteria of 226 population members using random sampling method. Probability sampling approach so that the number of samples studied is 70 data from January 1 to May 31, 2021. The data collection technique used is secondary data including documentation and literature study. The data analysis technique used is linear regression. Based on the results of this study, it shows that partially there is a significant influence of e-commerce marketing capabilities on the effectiveness of promotions then partially e-commerce marketing capabilities have a significant effect on competitive strategy and simultaneously e-commerce marketing capabilities have a significant effect on the effectiveness of promotions and strategies. compete in the MSME trade sector in Sukabumi City. Keywords: E-commerce Marketing Capability, Promotion Effectiveness, and Competitive Strategy